Die Gräberfelder in Samad al Shān (Sultanat Oman): Materialien zu einer Kulturgeschichte - Yule, Paul A. (Verlag Marie Leidorf, 1995)
HDR
Keywords: Archéologie – Oman

Pre-islamic archaeology of Kuwait, Northeastern Arabia, Bahrain, Qatar, United Arab Emirates and Oman: a bibliography. First supplement, 1985-1995 - Haerinck, Ernie; Stevens, Karel Guy (Peeters, 1996)
Keywords: Archéologie – Oman; Bibliographie – Oman

Names of Aromata in Semitic and Cushitic Languages - Banti, G.; Contini, R. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Il giardino del Dio - Betrò, M. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Perfumes and Power - Bowersock, G. W. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Incenso Mirra e Cinnamomo. Prodotti esotici nella farmacopea egiziana antica - Bresciani, E. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Evidence for the Use of Aromatics in the Early Bronze Age of Oman: Period III at RJ-2 (2300-2200 BC) - Cleuziou, Serge; Tozi, M. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

II ruolo dell'Arabia nel commercio delle spezie e dell'incenso: da Elio Gallo a Vosco da Gama - Costa, Paolo M. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Incense and Perfumes in the Late Bronze Age Aegean - D'agata, A. L. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

The Frankincense Road from Najrân to Ma'ân: a Hypothetical Itinerary - De Maigret, A. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Tus e murra: aromi sudarabici nella Roma arcaica - De Romanis, F. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

L'Egitto tolemaico e la terra degli aromata - Fantasia, U. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

The Contacts between Southern Arabia and the Horn of Africa in Late Prehistoric and Early Historical Times: a View from Africa - Fattovich, R. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

La produzione del balsamo nell 'oasi di Engaddi (Israele). Su alcuni nuovi documenti dal deserto di Giuda - Gnoli, T. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Kingship and Perfumes: Antiochus TV and Alexander the Great - Grottanelli, C. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Coppe e bracieri da incenso nell 'oriente classico - Invernizzi, A. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Beyond Deserts, beyond Oceans - Liverani, M. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Trade Routes and Trade Goods at the Northern End of the «Incense Road» in the first Millennium B.C. - Macdonald, M.C.A. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Complex Society, Urbanization and Trade: the Case of Eastern and Western Arabia - Mazzoni, S. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

The Harvesting of Frankincense in Dhofar, Oman - Morris, Miranda (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Les échanges entre l'Arabie du Sud et la péninsule d'Oman du 3ème siècle av. J.-C. au 4ème siècle ap. J.-C. - Mouton, Michel (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Namen von Aromata im antiken Süd-arabien - Müller, Walter W. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Do Anchors Mean Ships? Underwater Evidence for Maritime Trade along the Dhofar Coast, Southern Indian Ocean - Owen, J. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Al-Hâmid: a Route to the Red Sea? - Phillips, Carl (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

The Arab Connection. Political Implications of Frankincense in Early Greece - Retsö, J. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Arabie Méridionale: l'état et les aromates - Robin, C.J. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Profumo di terra: valori e simboli dell 'immaginario romano - Rosati, G. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Milan: Discovery of Frankincense Lumps in a Roman Burial - Rossignani, M. P. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Deux noms de mesures dans les textes sud-arabes sur bois - Ryckmans, J.; Drewes, A. J. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Dell'uso dell'incenso in epoca romana - Salmeri, G. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Sea-trade of the Hadramawt Kingdom from the 1st to the 6th Centuries A.D. - Sedov, A. V. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Caravans across the Eastern Desert of Egypt: Recent Discoveries on the Berenike-Apollinopolis Magna-Coptos Roads - Sidebotham, S. E. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Profumi e filosofia nell'Atene di Socrate - Soverini, L. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Un modo arcaico di produzione vetraria: viaggio nel tempo al seguito di unafonte contemporanea - Taborelli, L. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

L'incenso e gli incensieri nel mondo greco - Zaccagnino, C. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Notes sur l'Arabie dans les sources classiques - Zambrini, A. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Mesopotamia and Frankincense: the Early Evidence - Zarins, Juris (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Profumi d'Arabia: atti del convegno - Avanzini, Alessandra ("L'Erma" di Bretschneider, 1997)
Keywords: Archéologie – Oman

Archaeological Evidence of Overseas Contacts between Omani Traders and the Far East and the Outer World prior to the opening of the Cape Route - Costa, Paolo M. (The United Nations Educational Scientific and Cultural Organization (UNESCO) Project to study the Silk Routes : Papers submitted at the International Seminar on the Silk Roads held at Sultan Qaboos University, Muscat, Sultanate of Oman, 20-21 November 1990, 1992)
Keywords: Archéologie – Oman

Prehistoric Origins of Seafaring a long t he Oman Coast - Cleuziou, Serge (The United Nations Educational Scientific and Cultural Organization (UNESCO) Project to study the Silk Routes : Papers submitted at the International Seminar on the Silk Roads held at Sultan Qaboos University, Muscat, Sultanate of Oman, 20-21 November 1990, 1992)
Keywords: Archéologie – Oman

الفهرس الجغرافي لموقع الآثار في عمان عام 1967م - Cardi, Beatrice de (وزارة التراث القومي والثقافة, 1994)
Keywords: Archéologie – Oman

Medieval Qalhat: Travellers, Dhows and Stone Anchors in South-East Oman - Agius, Dionisius A. (Archaeology of Seafaring: The Indian Ocean in the Ancient Period, 1999)
This study presents the findings of a field trip conducted in 1998 to South-East Oman. The paper firstly looks into the writings of Medieval and Early Modern travellers who visited Qalhat and from their accounts study the types of vessels that were mentioned in connection with the Arabian-Persian Gulf and the Indian Ocean; secondly, to find from the local sailors the types and functions of dhows and what anchors were used for in the recent past. An attempt is made in the present study to reconstruct from the early writings the sea activity and its impact during the time period in question and to establish how much of the information given by the locals of South-East Oman can be corroborated by the findings related to the past.
Keywords: Archéologie – Oman

تراث عمان - Vein, Peter; Jones, Gigi Crocker (دار ايمل, 1995)
Keywords: Archéologie – Oman

Grave types and "triliths" in Dhofar - Shahrî, Ali Ahmad Ali Mahāsh al- (Arabian Archaeology and Epigraphy, 1991)
Keywords: Archéologie – Oman

Prehistoric Tower Tombs at Shir/Jaylah, Sultanate of Oman - Yule, Paul A.; Weisgerber, Gerd (Beiträge zur allgemeinen und vergleichenden Archäologie, 1998)
In 1995 survey was undertaken in the Sultanate of Oman in order to monitor the preservation to archaeological monuments. The work centred on over 58 tombs at Shir (Wilīyat Ṣūr). Five types of tombs were discerned. In their form and manner of building the towers the so-called beehive tombs of the Hafit Period, but also share certain resemblances with collective Umm an-Nar period tombs.
Keywords: Archéologie – Oman

Studies in the archaeology of the Sultanate of Oman - Yule, Paul A. (Verlag Marie Leidorf, 1999)
Keywords: Archéologie – Oman

The Samad Period in the Sultanate of Oman - Yule, Paul A. (Iraq, 1999)
Keywords: Archéologie – Oman

More than Samad in Oman: Iron Age pottery from Suhar and Khor Rori - Yule, Paul A.; Kervran, Monique (Arabian Archaeology and Epigraphy, 1993)
Keywords: Archéologie – Oman

Oman Expedition December 1995-January 1996 - Vosmer, Tom; Carpenter, Jon; Baker, Patrick (Western Australian Maritime Msueum, 1996)
Keywords: Archéologie – Oman

Mihrabs omanais du 16e siècle: un curieux exemple de conservatisme de l'art du stuc iranien des époques seldjouqide et mongole - Kervran, Monique; Bernard, Vincent (Archéologie Islamique, 1996)
Keywords: Archéologie – Oman

Musandam: an ethno-archaeological appreciation - Costa, Paolo M. (New Arabian Studies, 1993)
Keywords: Archéologie – Oman